Colposcopy and colpocytology: Auxiliary in the obstetrical and gynecological diagnosis - Ludmir, Abraham (2015)
As presentation work we wanted to raise in general canons, the use of two diagnostic methods: colposcopy and colpocytology, which at the time occupied a place of privilege in the specialty undisputed we grow. We are sure that these methods are well known by all of you, but it is possible that certain aspects, based on our experience and presented consistently, can serve clarifying concepts and refreshing ideas what our intention will be fulfilled. It is only the Colposcopía.- stereoscopic visualization of the cervix under magnification with direct lighting. It was Hinselman in 1925 which originally described the technique and has since been used with increasing frequency. Our learning and experience with the colposcope, we have obtained in Philadelphia. Dr. Warren Lang (disciple of Hinselman) with whom we conducted work in relation to vaginitis. The study is Colpocitología.- exfoliated cells, aspirates and flaking. Fixed with a specific dye and giving particular attention to nuclear and cytoplasmic morphology. In two previous papers presented one at the First Peruvian Congress of Obstetrics and Gynecology and the second as joining the Peruvian Society of marital fertility have exposed our experience regarding the role of this method in the diagnosis of benign conditions in the OB field and Gynecology.